Silver Nanoparticle as a Modern Era in Antimicrobial Activity - I, Shaikh Imran; Shafi, Dr Sameer; Kazi , Anis; Sante, Rohini; Jadhav, Avinash; Mohini, Gurav; Ritthe , Punam (Asian Journal of Pharmaceutical Research and Development, 2024)
In the modern era of antimicrobial research, silver nanoparticles (AgNPs) have emerged as promising agents with unprecedented potential. This abstract encapsulates the multifaceted role of silver nanoparticles in combating microbial threats. AgNPs exhibit unique physicochemical properties that contribute to their antimicrobial efficacy, including a high surface area-to-volume ratio and distinct electronic and optical behaviours. These characteristics enable diverse antimicrobial mechanisms, such as disrupting cell membranes, interfering with cellular processes, and inducing oxidative stress. Moreover, the size-dependent activities of AgNPs enhance their specificity against a broad spectrum of microorganisms, including bacteria, fungi, and viruses. The abstract delves into the diverse applications of silver nanoparticles in various fields, from healthcare to environmental protection. AgNPs have found utility in medical devices, wound dressings, and pharmaceutical formulations, showcasing their versatility in preventing and treating infections. Additionally, the abstract emphasizes the role of silver nanoparticles in water treatment and disinfection, underscoring their potential impact on public health. However, challenges such as cytotoxicity and environmental concerns warrant meticulous investigation and optimization in the design and application of AgNPs. The abstract concludes by acknowledging the imperative nature of ongoing research in unraveling the full potential of silver nanoparticles as a modern-era antimicrobial strategy, offering unprecedented solutions to combat the evolving challenges posed by microbial resistance in the contemporary world.